Pengaruh Variasi Kecepatan Udara Dan Penambahan Udara Bantu Pada Reaktor Terhadap Performa Kompor Gasifikasi Updraft Dengan Bahan Bakar Sekam Padi - Putranto, Yunanto Praba Budi, Wijianto, ST, M.Eng, Sc (2017)
Updraft gasifire is one on technology that used in gasification. The purpose of this research is to find out the effect of the air speed variation and addition of secondary air to reactor toward performance of updraft gasifire. This research use experiment of updraft gasifire in two ways, there are without and with addition of assist air to reactor.on every experiment on this research have been given variation of air speed. The variation of air speed in this experiment are 8 m/s, 10 m/s, 12 m/s then there will be measuring on roasting temperature, water temperature, and effective flame/ the outcome indicate higher air speed variation so higher roasting temperature and faster effective flame will be. Also addition assist air toward reactor will make higher thermal efficiency will be on air speed 12 m/s with thermal efficiency in the amount of 19,14%. Key word : updraft gasifire, air speed variation